Grupo ocupacional, nível educacional, status matrimonial e hábitos deletérios à saúde entre indivíduos com fraturas maxilofaciais: estudo retrospectivo em uma população do nordeste brasileiro - Esses, Diego Felipe Silveira (2016)
The epidemiological profile of trauma may reflect inequalities in health between groups. The objective of this study is to investigate the occupational profile, educational level, marital status and deleterious habits to the health of patients with maxillofacial fractures of a subpopulation of northeastern Brazil. a retrospective study of medical records of patients admitted to the Oral and Maxillofacial Surgery and Traumatology, University Hospital Walter Cantídio (Fortaleza, Ceará, Brazil), affected by maxillofacial fractures was conducted in the period between 2006 and 2015. We identified 338 patients who, in total showed 355 fractures. Males were the most affected (p <0.001) and the mean age was 31.3 +/- 12.9 years, with prevalence in the third decade of life (p <0.001). There was a predominance of motorcycle accidents (p <0.001), home workers as main occupation (p <0.001), low educational status (p = 0.032), and no cigarette use (p <0.001) or alcohol (p = 0.023) . Fractures of the zygomatic-orbital and mandibular complex were the most prevalent in the sample (p <0.001). Thus, we conclude that the socio-demographic profile, represented by educational level, occupation, marital status and deleterious habits, exerted influence on the epidemiological profile of maxillofacial fractures in a subpopulation of the Brazilian Northeast, during the study period.